Mechanical behaviour of a sandwich panel composed of hybrid skins and novel glass fibre reinforced polymer truss core. (1st May 2019) - Djama, Khaled; Michel, Laurent; Gabor, Aron; Ferrier, Emmanuel
Abstract: This study investigated the usability of hybrid sandwich structures as facade panels. The explored sandwich structure was made of mineral-glass fibre reinforced polymer (GFRP) skins and a GFRP truss core, fabricated by means of a novel manufacturing method. The compressive and shear specific strengths of the panels were assessed and compared with a few common lightweight structures to verify that the manufactured truss core had comparable values. Three-point bending tests indicated that the polyurethane foam used (required for the manufacturing process) had negligible mechanical contribution. Full-scale panels were tested under a distributed load. The tests were simulated using the three-dimensional finite element method to predict the pressure at which mineral cracks appeared in order to avoid their occurrence in the design phase. The simulation results exhibited good agreement with experimental data, and the model was validated in terms of deflection and strain responses. The occurrence of cracks and their propagation were numerically reproduced using the concrete-damage plasticity model. The link between the connector and crack positions in the mineral skin was highlighted in this study.